VIOLENCE AGAINST WOMEN, EQUALITY OF GENDER AND SOCIAL ETHICS - Fransiska Novita Eleanora (Diponegoro Law Review, 2018)
Humans are created interdependent and complement each other, as well as mutual respect and respect that is what is called a social creature, and live in pairs between men and women to continue offspring, which is a natural human nature that has been hereditary. But in reality, in social life, a woman often gets inhumane treatment, be it in public life or domestic life, is treated rudely, and impressed as not considered, women are very vulnerable to violence, whether physical violence, psychic violence, violence sexual even neglect of household. Or even men do not respect women in the realm of the outside or inside the dwelling. Result in a significant difference to gender equality itself. The most important and protected women's rights are freedom, being treated equally in the eyes of law, teaching and education is absolute, as well as health, legal certainty and justice and legal certainty. Social ethics arises in everyone, according to their nature and character. Human nature can be seen from their actions in treating and respecting others, especially treating the opposite sex, not in accordance with ethics and social sense, then the person is considered disrespectful to others.  The literature study is the method used in this study is to have a purpose to know gender and its equality be the cause of violence against women, and its relation to social ethics. The result is a patriarchal culture that assumes that men as rulers, while women are in a weak position or are perceived as "male" owners, and social ethics greatly affect respect for women, where social ethics strongly determines one's behavior and how to respect and respect for women's rights.